The Effect of Employer Branding and Career Development on Employee Retention with Job Satisfaction as A Mediation Variable on Generation Z in Special Region of Yogyakarta - Ayu Idawati; Ratri Nurina Widyanti (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the effect of employer branding and career development on employee retention with job satisfaction as a mediating variable among Generation Z employees in the Daerah Istimewa Yogyakarta. The high turnover rate among Generation Z has become a significant challenge for organizations, making it important to identify factors that influence their retention. A quantitative research design was employed using a survey method involving 100 Generation Z employees with a working tenure of 3 months to 1 year, selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.1.1.8. The findings reveal that employer branding and career development have a positive and significant effect on both job satisfaction and employee retention. Career development is identified as the most dominant predictor of employee retention. In addition, job satisfaction has a significant positive effect on employee retention and partially mediates the relationship between employer branding and career development on employee retention. The model demonstrates strong explanatory power with an R² value of 0.755, indicating substantial predictive relevance. These findings highlight that effective retention strategies for Generation Z require the integration of strong employer branding, structured career development systems, and sustained improvement in job satisfaction. This study contributes to Human Resource Management literature by providing empirical evidence on the importance of combining organizational attractiveness and career growth opportunities to retain young employees in a competitive labor market.